Penerapan Model Atik Untuk Meningkatkan Motorik Halus Pada Anak Di TK Muslimat Sindon - Devina Widi Astuti; Faqih Purnomosidi (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
Early childhood is a group of children who have very amazing personalities both in their growth and development processes. Children's cognitive development, religious and moral values, language, social-emotional, artistic and physical motor skills can develop well as a whole, namely a series of efforts to provide enthusiasm to increase potential specifically for aspects of early childhood development. Fine motor skills also have a relationship to performance in social functions and personal care of children and their relationships. Coloring activities are a demand and need for early childhood, because a child's development by coloring in various activities can fulfill a child's curiosity. The method of this service is lecture and discussion. The informants or subjects in this service are children who are kindergarten students at the Muslimat Sindon Kindergarten. The result of this service is fine motor skills through coloring activities using the ATIK model, children can express freedom in coloring but still within the game rules that have been previously prepared by the teacher. The conclusion from the dedication carried out by the author is that learning to color using the ATIK model has proven to be very effective and can improve fine motor skills in children at the Muslimat Sindon Kindergarten. Using this ATIK model, you can improve your ability to color, choose areas and colors that will be used to color image objects more enthusiastically and more fun.